Effect of aeration rate on oxygen transfer for leachate treatment / Muhamad Hasbullah Hassan Basri - Hassan Basri, Muhamad Hasbullah (2014)
Aeration process provides oxygen in leachate treatment as the purposes of increasing the dissolved oxygen consumption and allocation in the leachate components for microorganisms, organic and inorganic elements. Even there are various level of aeration rate have been introduce towards leachate treatment, the optimum or the efficient level of aeration rate still not satisfactory. The problem is the selection of aeration rate is still not suitable towards effect of oxygen transfer in the leachate treatment. As the current designed and studies on aeration rate, the optimum level of controlling the contamination of DO, BOD and COD in the leachate still not fully achieve and comply with the leachate effluent quality standard. This is bad for leachate effluent quality and the austerity of energy consumption, which amount of designed aeration rate or oxygen distribution, are not suitable for a range of leachate quality treatment. This study is significance to obtain critical or optimum design or comprehensions towards enhance the level of aeration rate in the treatment. The current research focuses on the evolution of optimum aeration rate, so as to yield higher values of oxygen transfers and aeration efficiency by varying some of physical and chemical indicators towards selection of optimum aeration rate in leachate treatment. The objectives of this study are for attain those requirements, to determine optimum aeration rate for leachate treatment, to determine the effect of aeration rate on oxygen transfer in leachate and to determine the effect of aeration rate on the water quality of leachate…